Multi-drug Resistant Streptococcus and Enterococcus Isolates from Central Abattoir Akinyele, Ibadan - Ayodeji, I, O.; Akanbi, I. O.; Oladele- Bukola, M. O.; Akanbi, I. M.; Kehinde, O. O.; Oyedepo, M. O.; Okuneye, J. O.; Emikpe, O. O.; Adekunle, O. F.; Lamidi, B. K.; Amusa, A. O.; Olofintuyi, O. K.; et al. (European Journal of Applied Sciences, 2024)
This study was designed to evaluate the antibiogram and resistance profile of Streptococcus and Enterococcus species isolated from the facilities and environment of the Central abattoir Akinyele, Ibadan, Oyo state, Nigeria. A total of sixty-four (64) samples were collected through the use of swab sticks on the knife and axe, scraping of the table and the cutting wood with sterile blade. The collected samples were cultured and isolated, while antimicrobial sensitivity testing was performed using Kirby Bauer disk agar diffusion method. This study shows that the prevalence of antimicrobial resistance of streptococcus species to the selected antibiotics; gentamicin (65%) and trimethoprim (58%), they showed the highest prevalence, while the lowest resistant was to ciprofloxacin (39%), on the contrary the enterococcus sp has the highest resistance prevalence with gentamicin (29%) while the least prevalence was with trimethoprim (7%). This study shows that ciprofloxacin has not been abused like other selected antibiotics for treating enterococcal infections. It can therefore be concluded that the water source and soil in the environment of the abattoir were contaminated with streptococcus and enterococcus species and were resistant to some of the selected antibiotics tested (oxytetracycline, gentamicin, enrofloxacin, ciprofloxacin, trimethoprim and amoxicillin). It is hereby recommended that there should be proper regulation and administration of antibiotics to prevent resistance development; and also there should be an improved personal and environmental hygiene.